Mental health in UK Biobank – development, implementation and results from an online questionnaire completed by 157 366 participants: a reanalysis - Davis, KAS; Coleman, JRI; Adams, M; Allen, N; Breen, G; Cullen, B; Dickens, C; Fox, E; Graham, N; Holliday, J; Howard, LM; John, A; et al. (Cambridge University Press, 2020)
Background UK Biobank is a well-characterised cohort of over 500 000 participants including genetics, environmental data and imaging. An online mental health questionnaire was designed for UK Biobank participants to expand its potential.